2019
DOI: 10.4103/eus.eus_42_18
|View full text |Cite
|
Sign up to set email alerts
|

Performance characteristics of EUS-FNA biopsy for adrenal lesions: A meta-analysis

Abstract: Background and Objective: The role of EUS-FNA biopsy (EUS-FNAB) for detection of metastatic lesions (mets) to adrenals has not been evaluated systematically. Our aim is to systematically evaluate the performance characteristics of EUS-FNAB in detecting metastasis to the adrenal glands. Materials and Methods: We performed a systematic search on PubMed and OvidSP from January 1990 to July 2016 using various search terms for EUS and adrenal lesion. Only articles published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The presence of an adenoma in left AG could have caused a false-positive in initial PET, but after ganciclovir treatment, no abnormal metabolic activity was detected in control PET. To our knowledge, this is the first case reported in the literature of unilateral CMV infection of AG in a non-HIV infected that have been diagnosed by EUS-FNA (1)(2)(3) . Given that PET scan hypercaptation is not always diagnostic of malignancy, it is mandatory to obtain pathological samples, of which EUS-FNA has proven the best technique (3) .…”
Section: Discussionmentioning
confidence: 75%
“…The presence of an adenoma in left AG could have caused a false-positive in initial PET, but after ganciclovir treatment, no abnormal metabolic activity was detected in control PET. To our knowledge, this is the first case reported in the literature of unilateral CMV infection of AG in a non-HIV infected that have been diagnosed by EUS-FNA (1)(2)(3) . Given that PET scan hypercaptation is not always diagnostic of malignancy, it is mandatory to obtain pathological samples, of which EUS-FNA has proven the best technique (3) .…”
Section: Discussionmentioning
confidence: 75%
“…Most current studies show results similar to the ones on this survey. For SMT lesions, suspected lymphomas, solid pancreatic masses, liver lesions, left adrenal gland lesions, and lymph nodes, histological evaluation has been recommended,[ 2 3 4 ] with the further possibility of performing immunohistochemical, phenotyping, or genetic analyses. For the above lesions, some studies have also demonstrated that FNB has advantages in tissue acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…EUS is widely used in the diagnosis and treatment of digestive tract diseases, as it allows for a clear view of the layered structure and thickness of the esophageal wall. [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ] This has unique diagnostic value for submucosal lesions, as it enables the identification of pseudo AC or secondary AC caused by venous tumors, neurofibroma, cicatricial stenosis, systemic sclerosis, sarcoidosis, or malignant neoplasms, reducing the likelihood of misdiagnosis and mistreatment. EUS can also be performed before and after POEM to determine the required degree of muscularis propria division.…”
Section: Diagnosis Of Achalasiamentioning
confidence: 99%